Formation of an Analytical Attitude to Information Among Students - Berdieva Gulobod Shonazarovna (Genius Journals, 2023)
In this state, the content and essence of understanding information, analysis, attitudes, and the formation of an idea of an analytical attitude to information are summarized. The state also describes the conditions for the formation of an analytical attitude to information of students
Keywords: information; analysis; attitude; education